The construction and use of kayaks in north-west greenland: preliminary report - Taylor, K. I. (Polar Record, 1961)
This paper is a report on the preliminary work of a long-term study of the construction, use and cultural significance of kayaks among Greenlanders living in the Umánaq area of north-west Greenland.